2018
DOI: 10.2147/dddt.s162014
|View full text |Cite
|
Sign up to set email alerts
|

Schisandrin B ameliorated chondrocytes inflammation and osteoarthritis via suppression of NF-κB and MAPK signal pathways

Abstract: IntroductionOsteoarthritis (OA) is the most prevalent joint disorder in the elderly population, and inflammatory mediators like IL-1β were thought to play central roles in its development. Schisandrin B, the main active component derived from Schisandra chinensis, exhibited anti-oxidative and antiinflammatory properties.MethodsIn the present study, the protective effect and the underlying mechanism of Schisan-drin B on OA was investigated in vivo and in vitro.ResultsThe results showed that Schisandrin B decrea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
61
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 75 publications
(62 citation statements)
references
References 26 publications
1
61
0
Order By: Relevance
“…The MAPK kinase p38, ERK and JNK were demonstrated to phosphorylate NR4A1 in other cell lines (Liu et al, 2007;Wang et al, 2009;Li et al, 2015). Our previous study has revealed that the inflammatory stimulation phosphorylated and activated MAPK p38, ERK and JNK in chondrocytes (Ran et al, 2018). In the present study, we observed that NR4A1 was phosphorylated in osteoarthritis tissue or through in vitro inflammatory stimulation, which was significantly blocked by p38, ERK and JNK inhibitors.…”
Section: Discussionsupporting
confidence: 59%
See 1 more Smart Citation
“…The MAPK kinase p38, ERK and JNK were demonstrated to phosphorylate NR4A1 in other cell lines (Liu et al, 2007;Wang et al, 2009;Li et al, 2015). Our previous study has revealed that the inflammatory stimulation phosphorylated and activated MAPK p38, ERK and JNK in chondrocytes (Ran et al, 2018). In the present study, we observed that NR4A1 was phosphorylated in osteoarthritis tissue or through in vitro inflammatory stimulation, which was significantly blocked by p38, ERK and JNK inhibitors.…”
Section: Discussionsupporting
confidence: 59%
“…Five sham surgeries and ten OA models were developed by simply opening joint cavity or surgical resection of the medial meniscus in SD rat (Male, 6 weeks old, specific pathogen free [SPF])knee joints as described previously (Ran et al, 2018). All the OA model animals were randomized into two groups: the experimental group (n = 5) and the control group (n = 5).…”
Section: Animal Experiments and Histological Analysismentioning
confidence: 99%
“…MAPK inhibitors blocked the joint inflammation and destruction in different osteoarthritis animal models [31]. Previous researches have provided ample proofs that the inhibition of the MAPK pathway inhibited the apoptosis and inflammatory response in human OA chondrocytes [22,32]. On the other hand, Sema4D weakened the phosphorylation of p-Erk1/2 in LPS-treated microglia [24].…”
Section: Discussionmentioning
confidence: 97%
“…Evaluation of joint cartilage is considered critical since the primary tissue degradation in KOA animal models that mimic human KOA occurs in this tissue; however, many studies have been limited. For example, in some KOA animal studies, only local assessment of the cartilage has been done using tissue sections and staining methods to assess cartilage degeneration quantitatively [4][5][6][7]. In addition, microscopic evaluation using India ink staining to confirm cartilage degradation in KOA animal models has demonstrated localized positive and non-positive areas [8][9][10].…”
Section: Introductionmentioning
confidence: 99%